Giant improper ferroelectricity in the ferroaxial magnet CaMn 7O 12 - Johnson, R; Chapon, L; Khalyavin, D; Manuel, P; Radaelli, P; Martin, C (2012)
In rhombohedral CaMn 7O 12, an improper ferroelectric polarization of magnitude 2870μCm -2 is induced by an incommensurate helical magnetic structure that evolves below T N1=90K. The electric polarization was found to be constrained to the high symmetry threefold rotation axis of the crystal structure, perpendicular to the in-plane rotation of the magnetic moments. The multiferroicity is explained by the ferroaxial coupling mechanism, which in CaMn 7O 12 gives rise to the largest magnetically induced, electric polarization measured to date. © 2012 American Physical Society.